PENGARUH EDUKASI VIA VIDEO ANIMASI TERHADAP PENGETAHUAN REMAJA TENTANG PENDEWASAAN USIA PERKAWINAN USIA PERKAWINAN DI SMAN 4 CIBINONG 2025 - Masitoh, Siti; Herdianti, Cyntia; Syam, Heriza; Jehanara, Jehanara; Kusumastuti, Ani (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Early marriage is a serious issue among adolescents, often made without adequate understanding of its consequences. This study aims to determine the effect of education using animated video media on increasing adolescents' knowledge about the Maturity Age of Marriage (PUP) at SMAN 4 Cibinong. The method used is a pre-experimental design with a one-group pretest-posttest approach, involving 89 twelfth-grade students selected through purposive sampling. Data were collected using a questionnaire administered before and after the intervention. The results showed that before the intervention, most respondents had moderate to low knowledge. After education, there was a significant increase to a good knowledge category, with a significance value of < 0.001. The conclusion of this study is that education using animated video is effective in increasing adolescents' knowledge about PUP, aligning with the visual learning style of today's youth.